BL_GERICHTE 470 2011 225 vom 30. Juni 2005 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Strafrecht vom 7. Februar 2012 (470 11 225) - BL Gerichte (2005)
Verfahrenseinstellung (Teileinstellung)